Comparative Legal Analysis of Beauty Clinic Services between Indonesian Law and Islamic Law - Sari, Siska Diana (Indonesian Comparative Law Review, 2024)
In line with the evolving needs of consumers who strive to improve their facial and physical appearances, beauty clinics frequently introduce new services supported with new technological devices. Some forms of esthetical treatment introduced in the market have risen controversy in terms of their legality. This article aims at  exploring the legality of esthetic treatment provided by beauty clinics from  the perspective of Indonesian law and Islamic law. This normative legal research employs comparative approach. Comparison is made between Indonesian law and Islamic Law. It is found that Islamic law has different approach in addressing the issue of the legality of esthetic treatment provided by beauty clinics as compared to Indonesian law.  While the Indonesian law tends to liberate various kinds of esthetic treatment, Islamic law gives a restriction. By virtue of the principle of freedom of contract as intended in Article 1338 of the Indonesian Civil Code, any esthetic treatment can be carried out when it is made based on a valid contract between the contracting parties. On the other side, Islamic Law prohibits particular esthetic treatment especially when it falls under the category of “changing what Allah has created.”